Planejamento ambiental de ecossistemas lacustres litorâneos em áreas protegidas: o caso da Área de Proteção Ambiental do Lagamar, litoral norte fluminense, Brasil - Luana Aparecida Castro Firmino; Eduardo Manuel Rosa Bulhões. (Confins)
Coastal lake ecosystems are important environmental, social, and economic value environments, but volatile and sensitive to human activities. In Brazil, these environments are governed by a broad and complex legal framework that, although it exists, does not guarantee that these spaces are effectively protected. One of the main means used to guarantee the protection of relevant natural areas is creating protected areas that use environmental planning as a spatial planning and organization tool to harmonize uses and thus maintain the balance between natural and human systems. This article aims to contribute to the discussion around the environmental planning of lake ecosystems inserted in protected areas and apply the integrated landscape analysis methodology based on systemic and geoecological criteria to propose actions and develop public policies in these areas. The study area chosen covers a legally protected coastal lake, located in the municipality of Campos dos Goytacazes, in the northern region of Rio de Janeiro. The results show the current situation and the state of environmental degradation of the landscape units and bring a proposal for zoning for this area's future scenario in question. The analysis approach employed proved to be effective for the planning proposition. It was possible to observe the evolution and the current situation of the environment, being an important instrument of management and public policies for coastal wetlands.